Ethnocomputational creativity in STEAM education: a cultural framework for generative justice - Audrey Grace Bennett (Revista Teknokultura, 2016)
In the United States, the disciplines of science, technology, engineering, and mathematics (also widely known as STEM) attract very few African American, Latino, and Native (indigenous Alaskan, North American, and Pacific Islander) students. These underrepresented students might be more attracted to STEM disciplines if they knew STEM education’s extraordinary potential to circulate value back to their ethnic communities. For instance, underrepresented medical students, after graduation, are statistically more likely than white students to conduct research on health issues relevant to their ethnic communities. One of the most popular STEM reform movements that of STEAM (STEM + Arts) has done very little to help circulate the unalienated value of these ethnic communities. This paper describes “ethnocomputational creativity” as a generative framework for STEAM that circulates unalienated value in the arts back to underrepresented ethnic communities. We first will look at the dangers of extracting cultural capital without compensation, and how ethnocomputational creativity can, in contrast, help these communities to circulate value in its unalienated form, nurturing both traditional artistic practices as well as creating new paths for "heritage algorithms" and other forms of decolonized STEM education.